2010
DOI: 10.1073/pnas.0913650107
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of xenotropic murine leukemia virus-related virus (XMRV) to retroviral restriction factors

Abstract: Xenotropic murine leukemia virus-related virus (XMRV) is a recently discovered gammaretrovirus that has been linked to prostate cancer and chronic fatigue syndrome. This virus is therefore an important potential human pathogen and, as such, it is essential to understand its host cell tropism. Intriguingly, infectious virus has been recovered from patient-derived peripheral blood mononuclear cells. These cells express several antiviral restriction factors that are capable of inhibiting the replication of a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
90
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 57 publications
14
90
2
Order By: Relevance
“…This finding is consistent with a recent study, which shows XMRV infection of the benign prostatic epithelial (PrEC) and stromal (PrSC) cells that may consist of fibroblast cells, as well as other cell types in the stroma (12). Related studies have similarly documented XMRV infection of not only prostatic stromal fibroblasts (PrSC) but also human cells of many different tissue types (11,37), as well as cells from various animal species (37). The authors of these studies have proposed that the in vivo susceptibility to XMRV cannot be determined by the Xpr1 receptor expression alone but that the ability of different cell types to either transactivate the XMRV viral promoter or to restrict virus replication define how efficient the virus can spread in certain tissues (11).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This finding is consistent with a recent study, which shows XMRV infection of the benign prostatic epithelial (PrEC) and stromal (PrSC) cells that may consist of fibroblast cells, as well as other cell types in the stroma (12). Related studies have similarly documented XMRV infection of not only prostatic stromal fibroblasts (PrSC) but also human cells of many different tissue types (11,37), as well as cells from various animal species (37). The authors of these studies have proposed that the in vivo susceptibility to XMRV cannot be determined by the Xpr1 receptor expression alone but that the ability of different cell types to either transactivate the XMRV viral promoter or to restrict virus replication define how efficient the virus can spread in certain tissues (11).…”
Section: Discussionsupporting
confidence: 80%
“…Related studies have similarly documented XMRV infection of not only prostatic stromal fibroblasts (PrSC) but also human cells of many different tissue types (11,37), as well as cells from various animal species (37). The authors of these studies have proposed that the in vivo susceptibility to XMRV cannot be determined by the Xpr1 receptor expression alone but that the ability of different cell types to either transactivate the XMRV viral promoter or to restrict virus replication define how efficient the virus can spread in certain tissues (11). Recent studies have also shown that XMRV infectivity can be limited by the presence of known host restriction factors to retroviral replication, such as the human APOBEC3 and tetherin proteins, as well as mouse APOBEC3, tetherin, and Fv1 proteins (11,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive serological fi ndings from previous studies may have also been the result of cross reactions 7 ; however, antibodies specifi c to the virus were apparently detected 8,9 . Other studies showed a prevalence of between 1-3% in the general (i.e., healthy) population, which indicated a possible role of blood transfusions in the dissemination of the virus 10,11 .…”
Section: Xenotropic Murine Leukemia Virus-related Virus Proteinsmentioning
confidence: 87%
“…Tetherin forms a bridge between virions and the plasma membrane (Sato et al, 2009). Tetherin contributes to antiviral activity against various enveloped viruses, including Ebola, Marburg, Lassa, KSHV, HIV-1, HIV-2, SIV, MLV, E1AV, VSV, HTLV-1, XMRV, and spumaviruses ( Jouvenet et al, 2009;Kaletsky et al, 2009;Le Tortorec and Neil, 2009;Mansouri et al, 2009;Miyakawa et al, 2009;Sakuma et al, 2009;Groom et al, 2010;Weidner et al, 2010;Xu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%